Employees’ green behaviour initiatives and green human resource management implementation challenges - Samson Adewumi (International Journal of Academe and Industry Research)
The green behaviour and green human resource management literature shows a sparsity of studies related to employee green behaviour initiatives and green human resource management implementation challenges, specifically in the context of Nigeria’s manufacturing organisations. Hence, this study seeks to address this gap by interrogating employees’ perception and understanding of green behaviour, green behaviour initiatives and green human resource management implementation challenges from the perspective of a manufacturing organization in Lagos, Nigeria. The case study research design was adopted with 15-unit managers purposively recruited from the human resource department and the semi-structured interview was employed to retrieve qualitative data from respondents. Themes and sub-themes were identified from the qualitative data with the aid of the NVivo (v.14) qualitative software. Findings include environmental sustainability, response to climate change and efficient use of raw materials as a perception and understanding of green behaviour. Managers understanding of green behaviour, awareness and campaigns, collectivism and consistent reviews and accountability of green project funds were revealed as green behaviour initiatives. Green human resource management implementation challenges include green evaluation and monitoring, socio-cultural constraints, personality and socialisation and education and training. The study concludes with a more strategic evaluation and monitoring of green behaviour policy and implementation. The policy implication is a call for the inclusion of green behaviour and personality tests in recruitment policy. This will help identify prospective employees with deviant to green behaviour compliance.